Topics of Women in the Iraqi Newspaper (Al- Sabah): (Feminist Approach) - Sabeeh, Azhar (ALBAHITH ALALAMI, 2020)
The search tried to achieve a major scientific goal represented by (Knowing the perspective that has been treated through press releases of woman articles in Al- Sabah newspaper), via: Specifying the rate of woman topics in Al-Sabah newspaper, compared with the other subjects. Revealing the nature of the topics of the woman that the newspaper dealt with. Identifying the ID of journalistic-product that dealt with the woman topics. Knowing the journalistic arts that the woman topics have been treated by. Standing on the cases which woman topics concentrated on, through Al-Sabah newspaper. The Research considers one of the descriptive researches depending on the (survey approach) with using the method of (analyzing the content) for woman topics that published in the Newspaper of Al-Sabah. The objective field of the research has been specified in the Iraqi Newspaper Al-Sabah. While its periodical aspect is represented in the limited period between two dates of (20-31) January, (10-19) February, and (2-12) March of the Year 2013. The Research reached to several conclusions: The Woman topics never shown as a fix, united content as part of a media strategy that adopts the feminist perspective as starting point for dealing and drawing the attention of the newspaper in question. But, the woman topics shown randomly and emergently in that Newspaper at best cases when they were a means to achieve certain institutional goals only. Deceasing the rate of woman topics that was treated by Al-Sabah Newspaper comparing with all other topics. The relative superiority of the light topics that belong to the woman at the expense of the serious topics. Retreating the woman in producing her own topics. Meanwhile the man progress comes quantitatively as a product to her topics. The prevalence of routine journalistic coverage of woman’s topics through the art of transferring the news that has come on a documentary way without any professional, deep treatment for its contents, that was at the expense of other journalistic arts. Dominating the style of floating in topics on the journalistic treatment method of woman topics. The search never pointed out, except in so rare cases, journalistic, direct and accurate treatments for woman cases especially the core ones, like the cases of education or vital activity within the political space.